2015
DOI: 10.1167/15.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual biases and cue weighting in perception of 3D slant from texture and stereo information

Abstract: Multiple cues are typically available for perceiving the 3D slant of surfaces, and slant perception has been used as a test case for investigating cue integration. Previous evidence suggests that texture and stereo slant cues contribute in an optimal Bayesian manner. We tested whether a Bayesian model could also account for perceptual underestimation of slant from texture. One explanation proposed by Todd, Christensen, and Guckes (2010) is that slant from texture is based on an inaccurate optical variable. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(60 citation statements)
references
References 42 publications
7
53
0
Order By: Relevance
“…Previous studies have found that slant from texture is underestimated with monocular viewing (Saunders, 2003;Todd et al, 2005;Watt et al, 2005;Norman et al, 2009;Durgin, Li & Hajnal, 2010;Saunders & Chen, 2015), and the underestimation is greater when texture information is degraded (Saunders, 2003;Rosas et al, 2004;Todd et al, 2005;Saunders & Chen, 2015). One possible explanation is that texture information is integrated with prior knowledge or frontal cues (e.g., accommodation), resulting in biases toward frontal when texture information is unreliable (Saunders & Chen, 2015).…”
Section: The Present Studymentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have found that slant from texture is underestimated with monocular viewing (Saunders, 2003;Todd et al, 2005;Watt et al, 2005;Norman et al, 2009;Durgin, Li & Hajnal, 2010;Saunders & Chen, 2015), and the underestimation is greater when texture information is degraded (Saunders, 2003;Rosas et al, 2004;Todd et al, 2005;Saunders & Chen, 2015). One possible explanation is that texture information is integrated with prior knowledge or frontal cues (e.g., accommodation), resulting in biases toward frontal when texture information is unreliable (Saunders & Chen, 2015).…”
Section: The Present Studymentioning
confidence: 98%
“…These plaid textures provide texture compression and scaling cues with or without the aligned spectral components, so any observed differences could be attributed to the orientation information provided by these components. Observers viewed planar surface patches with different slants and performed a manual slant estimation task (Saunders & Chen, 2015). In Experiment 1, we used a medium size FOV (168), and in Experiment 2 we used a smaller FOV (68) that is closer to the size of the stimuli used by Tam et al (2013).…”
Section: The Present Studymentioning
confidence: 99%
See 3 more Smart Citations